2010
DOI: 10.1158/1535-7163.mct-09-0952
|View full text |Cite
|
Sign up to set email alerts
|

Stage 2 Combination Testing of Rapamycin with Cytotoxic Agents by the Pediatric Preclinical Testing Program

Abstract: Rapamycin demonstrated broad-spectrum tumor growth inhibition activity against the in vivo panels of childhood tumors used in the Pediatric Preclinical Testing Program (PPTP). Here we have evaluated rapamycin combined with agents used frequently in the treatment of childhood malignancies. Rapamycin was tested in vitro against 23 cell lines alone or in combination with melphalan, cisplatin, vincristine, or dexamethasone (leukemic models only). In vivo, the impact of combining rapamycin with a cytotoxic agent wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
89
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 32 publications
0
89
0
Order By: Relevance
“…In other studies, mTOR inhibition was also shown to sensitize cancer cells to chemotherapy, including pediatric sarcoma models. 24,25 Moreover, the mTOR inhibitor everolimus dramatically enhanced cisplatin-induced apoptosis in wildtype p53, but not mutant p53, tumor cells. 26 Both OS-1 and OS-33 models are p53-wildtype, as is the majority (62%) of clinical osteosarcoma samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other studies, mTOR inhibition was also shown to sensitize cancer cells to chemotherapy, including pediatric sarcoma models. 24,25 Moreover, the mTOR inhibitor everolimus dramatically enhanced cisplatin-induced apoptosis in wildtype p53, but not mutant p53, tumor cells. 26 Both OS-1 and OS-33 models are p53-wildtype, as is the majority (62%) of clinical osteosarcoma samples.…”
Section: Discussionmentioning
confidence: 99%
“…Additive efficacy was reported in one out of two osteosarcoma models, but excessive toxicity was observed in these models as well. 24 Rapamycin combined with cisplatin also resulted in excessive toxicity. However, at lower doses of cisplatin, rapamycin potentiated cisplatin activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group, and others, have demonstrated that rapalogs have an additive or synergistic effect when combined with many agents in vitro, including methotrexate, corticosteroids, doxorubicin, etoposide, and asparaginase. [136,[144][145][146] An added benefit was not found when rapalogs were combined with vincristine in vitro; however, the combination was found to be more effective than either drug alone in vivo. [136,139,146] Rapalogs have been studied in vivo in combination with methotrexate and corticosteroids.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 99%
“…Rapamycin (RAPA) is the special inhibitor of mTOR, which has demonstrated anti-tumor effects in a variety of malignancies in preclinical and clinical studies. In addition to being used as a monotherapy, RAPA and its analogs have been shown to enhance the efficacy of a number of cytotoxic chemotherapeutic agents in various types of cancer (8)(9)(10)(11). Studies have shown that the anti-tumor mechanism of RAPA includes both apoptosis and autophagy, and its role in the fate of cancer cells remains controversial (12).…”
Section: Introductionmentioning
confidence: 99%